Pembinaan Tahsin Al-Qur'an untuk Pengenalan dan Pelafalan Huruf Hijaiyah di Madrasah Diniyah Takmiliyah Misbahus Sudur - Abd. Basid; Qurrotul Layyinah; Ahmad Kholilurrohman (Unity Academy, 2024)
The lack of understanding of makharijul huruf and tajwid among students at Madrasah Diniyah Takmiliyah Misbahus Sudur affects the quality of Quranic recitation. The issue includes errors in pronouncing Hijaiyah letters and improper application of tajwid rules. The objective of this Community Service Program (PkM) is to enhance students' Quranic reading skills through the talaqqi method, which involves direct face-to-face teaching between teacher and student. The training was attended by 16 students and conducted three times a week, with additional practice sessions on other days. The materials covered included the introduction of Hijaiyah letters, makharijul huruf, and tajwid rules, delivered through direct practice and repetitive drills. The results showed significant improvement, with 90% of students able to pronounce Hijaiyah letters correctly and 85% of students successfully applying basic tajwid rules in their Quranic recitation. However, challenges remain in the form of limited availability of qualified teachers. The conclusion emphasizes the importance of integrating makharijul huruf and tajwid learning into the madrasah curriculum and calls for further support from relevant stakeholders to address the shortage of trained teachers. With the right approach, students are expected to read the Quran more accurately and correctly according to tajwid principles.